2017
DOI: 10.1175/jamc-d-16-0136.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Correct Radiosonde Temperature Biases Using Radio Occultation Data

Abstract: A new method to estimate radiosonde temperature biases using radio occultation measurements as a reference has been developed. The bias is estimated as the difference between mean radio occultation and mean radiosonde departures from collocated profiles extracted from the Met Office global numerical weather prediction (NWP) system. Using NWP background profiles reduces the impact of spatial and temporal collocation errors. The use of NWP output also permits determination of the lowest level at which the atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Wong et al (2015) used ECMWF forecasts for double-differencing to reduce the sampling differences between Atmospheric Infrared Sounder (AIRS) and RS co-located pairs. Tradowsky et al (2017) calculated an observed-background (O-B) double difference to estimate the mean RS temperature bias using co-located RO profiles and Met Office model background fields. These studies use a double-difference correction, but do not verify or discuss how the correction reduces sampling errors.…”
Section: Spatial-temporal Sampling Correction Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Wong et al (2015) used ECMWF forecasts for double-differencing to reduce the sampling differences between Atmospheric Infrared Sounder (AIRS) and RS co-located pairs. Tradowsky et al (2017) calculated an observed-background (O-B) double difference to estimate the mean RS temperature bias using co-located RO profiles and Met Office model background fields. These studies use a double-difference correction, but do not verify or discuss how the correction reduces sampling errors.…”
Section: Spatial-temporal Sampling Correction Algorithmmentioning
confidence: 99%
“…However, as the equivalent Eq. (6a) shows, the corrected difference is also the difference of the departures of the two data sets from a common, reference data set, or the "double-differencing" method (Chander et al, 2013;Tradowsky et al, 2017). In this interpretation, the two data sets are not necessarily required to be close in space or time; the method is valid as long as the biases of the reference data set do not vary over the spatial and temporal scales of the comparison.…”
Section: Spatial-temporal Sampling Correction Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Wong et al (2015) used ECMWF forecasts to estimate the sampling differences between Atmospheric Infrared Sounder (AIRS) and RS co-located pairs, using a double-difference error estimate to correct AIRS and RS differences. Tradowsky et al (2017) Office NWP background fields, in which the double-difference is applied to reduce the effects of temporal and spatial sampling errors. These studies use a double-difference sampling correction, but do not verify or discuss how the correction reduces sampling errors.…”
Section: Spatial Correction Algorithmmentioning
confidence: 99%
“…By subtracting the model data from both the RO and RS the background and representativeness errors are removed, leaving only the RO and RS observational errors. The approach has been called the "double-difference" method (Haimberger et al, 2012;Wong et al, 2015;Tradowsky et al, 2017). In addition 2 Atmos.…”
Section: Introductionmentioning
confidence: 99%